Mining for liquid gold: midwifery language and practices associated with early breastfeeding support - Elaine Burns; Jenny Fenwick; Athena Sheehan; Virginia Schmied (Maternal and Child Nutrition)
Abstract Internationally, women give mixed reports regarding professional support during the early establishment of breastfeeding. Little is known about the components of midwifery language and the support practices, which assist or interfere with the early establishment of breastfeeding. In this study, critical discourse analysis has been used to describe the language and practices used by midwives when supporting breastfeeding women during the first week after birth. Participant observation at two geographically distant Australian health care settings facilitated the collection of 85 observed audio‐recorded dyadic interactions between breastfeeding women and midwives during 2008–2009. Additionally, 23 interviews with women post discharge, 11 interviews with midwives and four focus groups (40 midwives) have also been analysed. Analysis revealed three discourses shaping the beliefs and practices of participating midwives. In the dominant discourse, labelled ‘Mining for Liquid Gold’, midwives held great reverence for breast milk as ‘liquid gold’ and prioritised breastfeeding as the mechanism for transfer of this superior nutrition. In the second discourse, labelled ‘Not Rocket Science’, midwives constructed breastfeeding as ‘natural’ or ‘easy’ and something which all women could do if sufficiently committed. The least well‐represented discourse constructed breastfeeding as a relationship between mother and infant. In this minority discourse, women were considered to be knowledgeable about their needs and those of their infant. The language and practices of midwives in this approach facilitated communication and built confidence. These study findings suggest the need for models of midwifery care, which facilitate relationship building between mother and infant and mother and midwife.